Prevalence and possible risk factors of peri-implantitis: a concept review - Marcantonio, Claudio [UNESP]; Nicoli, Lelis Gustavo [UNESP]; Marcantonio Junior, Elcio [UNESP]; Zandim-Barcelos, Daniela Leal [UNESP] (Jaypee Brothers Medical Publishing, 2015)
The purpose of this review is to estimate the prevalence of peri-implantitis, as well as to determine possible risk factors associated with its development in patients treated with oral implants. Although implant therapy has been identified as a successful and predictable treatment for partially and fully edentulous patients, complications and failures can occur. Peri-implantitis is considered a biologic complication that results in bone loss around implants and may lead to implant treatment failure. A great variation has been observed in the literature regarding the prevalence of peri-implantitis according to the diagnostic criteria used to define peri-implantitis. The prevalence ranges from 4.7 to 43% at implant level, and from 8.9 to > 56% at patient level. Many risk factors that may lead to the establishment and progression of peri-implantitis have been suggested. There is strong evidence that presence and history of periodontitis are potential risk factors for peri-implantitis. Cigarette smoking has not yet been conclusively established as a risk factor for peri-implantitis, although extra care should be taken with dental implant in smokers. Other risk factors, such as diabetes, genetic traits, implant surface roughness and presence of keratinized mucosa still require further investigation. Peri-implantitis is not an uncommon complication following implant therapy. A higher prevalence of peri-implantitis has been identified for patients with presence or history of periodontal disease and for smokers. Until now, a true risk factor for peri-implantitis has not been established. Supportive maintenance program is essential for the long-term success of treatments with oral implants. The knowledge of the real impact of peri-implantitis on the outcome of treatments with oral implants as well as the identification of risk factors associated to this inflammatory condition are essential for the development of supportive maintenance programs and the establishment of prevention protocols.
Keywords: Dental implants; Implant success; Peri-implantitis; Prevalence; Risk factor